Johanna Kandl : Das geschlossene System. (Krems : Kunsthalle Krems, 1993)
Andelkovic, Dejan ; Bajic, Mrdan ; Brkanovic, Jasminka ; Cekic, Jovan ; Ilic, Marija ; Iljovski, Bora ; Joksimovic, Zdravko ; Kacic, Darija ; Knezevic, Radomir ; Knezevic, Stevan ; Knezevic, Vesna ; Krnajski, Dragoslav ; Markovic, Sasa ; Pecic, Dimitirje ; Prodanovic, Mileta ; Radovanovic, Jelica ; Roksandic, Sloboban ; Grupa Skart ; Stevanovic, Milica ; Stevanovic, Vera ; Todic, Milanka
Johanna Kandl : Das geschlossene System, Kunsthalle Krems, 1993
boek
Keywords: Kandl, Johanna; Belgrado